A journey of diversity & inclusion in South Africa : Guidelines for leading inclusively. - Molefi, Nene (KR Publishing, 2017)
A Journey of Diversity & Inclusion in South Africa is a groundbreaking new book that addresses inequality, prejudice, injustice, racism, sexism and all other forms of discrimination in society, and in particular the workplace, in a positive way. Using entertaining stories from her own experience and a light-hearted writing style, diversity expert Nene Molefi offers a comprehensive approach to help any organisation achieve a more inclusive and positive working environment.-- Publisher's website.